The effect of relationship marketing on customer loyalty towards fast food restaurants (a study of generation Y) / Ahmad Zulfa Mohd Kamil and Muhammad Afif Mahabob - Mohd Kamil, Ahmad Zulfa; Mahabob, Muhammad Afif (Faculty of Business Management, 2016)
Intense competition in the business environment forces firms to look for the best approach to attract and create loyal customers. Relationship marketing is a strategy used by many firms to maintain long-term relationship with customers. Good implementation of relationship marketing strategies will result in quality relationship built between customers and firms. This study attempts to investigate the relationship between relationship marketing dimensions and loyalty towards fast food restaurants among Generation Y. Four key dimensions of relationship marketing are considered in this study which are trust, communication, commitment and empathy. The study was conducted in Bandaraya Melaka with a sample of 150 respondents. Sampling method used in this study is convenience sampling. The data was analysed using correlation coefficient and regression by using SPSS software. The findings reveal that are positive relationship between these relationship marketing dimensions and customer loyalty. However, the result shows that only commitment has significant impact on customer loyalty.